Methodology for net profitability analysis - Labonaitė, Gintarė; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2014)
Every company, regardless of the type or size of business is aiming to achieve the best results. These results are usually related to the profit and the ways to improve it. However, profit line in absolute terms is not sufficient enough as an indicator of the company’s performance. Therefore, instruments expressed in profitability ratios are used. While different authors reveal various aspects of the concept of profitability, overall profitability ratios could be assessed as the evaluation of activities‘ results and the relationship of the means used to achieve it. Net profitability ratio is one of the main cornerstones in the process of company‘s performance evaluation. It provides information on the efficiency of company‘s main, other, financial and investment activities - the final result. In addition, the ratio helps to evaluate efficiency of financial resources management. The analysis of net profitability ratio and factors influencing it may help to determine which element could be adjusted or changed in order to improve the company‘s performance and to gain higher profits. The article investigates evaluation of net profitability, provides methodology for net profitability analysis, based on the summary of the various authors researches of pyramid systems on influence of various factors to the subject ratios. Methodology of net profitability analysis includes such stages as selection of companies for comparison of information, assessing information sources, application of pyramid analysis system, evaluation of results based on selected company‘s data and data of Department of Statistics, conclusions and suggestions. Chosen ratios of pyramid analysis, which reveal factors affecting the net profitability, reflects aspects of evaluation of efficiency of the assets, equity and current assets to equity ratio. Information collecting, comparison, grouping, systematization, generalization and pyramid analysis methods were used in the research.